2019
DOI: 10.1080/09593985.2019.1641864
|View full text |Cite
|
Sign up to set email alerts
|

How do physiotherapists solicit and explore patients’ concerns in back pain consultations: a conversation analytic approach

Abstract: Background: Guidelines advocate that non-specific chronic low back pain (NSCLBP) be considered within a multi-dimensional bio-psychosocial (BPS) framework. This BPS approach advocates incorporating the patient's perspective as part of the treatment process. 'Agenda setting' has been introduced as the key to understanding patients' concerns in medical encounters; however, this has received little attention in physiotherapy. This study explored how physiotherapists solicit and respond to the agenda of concerns t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 70 publications
1
30
1
Order By: Relevance
“…Physical therapists acknowledge the need for a person-centered approach to care but continue to have difficulty implementing many components of person-centered care ( 22 ). The patient-physical therapist interaction is often characterized as practitioner dominant with physical therapists finding it challenging to balance their own agendas with that of the patient ( 52 , 53 ). Coach2Move is an evidence-based intervention for physical therapists in which person-centered care is foundational and improves clinical outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapists acknowledge the need for a person-centered approach to care but continue to have difficulty implementing many components of person-centered care ( 22 ). The patient-physical therapist interaction is often characterized as practitioner dominant with physical therapists finding it challenging to balance their own agendas with that of the patient ( 52 , 53 ). Coach2Move is an evidence-based intervention for physical therapists in which person-centered care is foundational and improves clinical outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using documentation during the interaction is a widely recognized barrier to effective communication (Cowell, McGregor, et al, 2019; Schoeb & Hiller, 2018). In these findings, the physiotherapists’ sensitivity to the intrusive nature of documentation was manifest in their body comportment and eye gaze away from the documentation and toward the patient (Robinson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Physiotherapists were typically found to follow their own agenda, however, when a more collaborative, shared conversation style was pursued, patients were allowed to describe their concerns more fully. 59 Physiotherapists that engaged in postgraduate clinical conversation training demonstrated very positive feedback along with an increase in patient satisfaction in the service that those physiotherapists worked. 60 Research has demonstrated that people experiencing pain report that they do not always feel listened to or believed by healthcare professionals (physiotherapists included).…”
Section: Line Of Argument 1: Train Physiotherapists To Encourage and Facilitate Conversation About Painmentioning
confidence: 98%